KEEFEKTIFAN LAYANAN BIMBINGAN KELOMPOK BERMUATAN NILAI SAPRAHAN UNTUK MENINGKATKAN RASA PERSATUAN SISWA DI SMP NEGERI 11 PONTIANAK - Nadia, Lia; Halida; Amallia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low sense of unity among students, characterized by increasing individualism, low social participation, and a lack of tolerance in school interactions. This research is based on the theory of group guidance (Prayitno) and the concept of saprahan values ​​as local wisdom, which emphasizes togetherness, mutual cooperation, religiosity, and strengthening social character. The method used was an experimental design with a pre-experimental design with a one-group pretest and posttest design. The subjects were eight students from SMP Negeri 11 Pontianak, selected purposively. Data collection used a Likert-scale questionnaire to measure the level of unity before and after the treatment. Data analysis was conducted using normality tests, homogeneity tests, and paired sample t-tests. The results showed an increase in the average sense of unity score from 68.63 to 76.88, with an average increase of 40%. The statistical test showed a significance value of p = 0.042 (<0.05), thus accepting the alternative hypothesis. This finding proves that group guidance services containing Saprahan values ​​are effective in increasing students' sense of unity. Therefore, integrating Saprahan values ​​into guidance services can be an innovative strategy for strengthening the sense of togetherness in schools.